Pink marine sediments reveal rapid ice melt and Arctic meltwater discharge during Dansgaard-Oeschger warmings - Rasmussen, Tine Lander; Thomsen, Erik (Nature Communications, 2013)
The climate of the last glaciation was interrupted by numerous abrupt temperature fluctuations, referred to as Greenland interstadials and stadials. During warm interstadials the meridional overturning circulation was active transferring heat to the north, whereas during cold stadials the Nordic Seas were ice-covered and the overturning circulation was disrupted. Meltwater discharge, from ice sheets surrounding the Nordic Seas, is implicated as a cause of this ocean instability, yet very little is known regarding this proposed discharge during warmings. Here we show that, during warmings, pink clay from Devonian Red Beds is transported in suspension by meltwater from the surrounding ice sheet and replaces the greenish silt that is normally deposited on the north-western slope of Svalbard during interstadials. The magnitude of the outpourings is comparable to the size of the outbursts during the deglaciation. Decreasing concentrations of ice-rafted debris during the interstadials signify that the ice sheet retreats as the meltwater production increases.